Post-Graduate Students’ Perceptions of Quillbot Utilization in English Academic Writing Class - Eka Yuni Kurniati; Rahmah Fithriani (Journal of English Language Teaching and Linguistics, 2022)
Academic writing is currently a worldwide concern. A plethora of studies on academic writing difficulties in higher education has been conducted. With the advancement of technology, the challenges of academic writing can be alleviated by using Quillbot, an artificial intelligence (AI)-powered digital tool. However, research on using Quillbot in post-graduate academic writing classrooms is still limited, and little is known about how students perceive it. This study investigates how post-graduate students view Quillbot as a digital tool for English academic writing. This study employed a qualitative case study design by involving 20 post-graduate students majoring in English education who were already familiar with Quillbot to participate. In investigating the participants' perspectives, a questionnaire and semi-structured interview were used as the instruments for data collection. The findings reveal that the post-graduate students in this study responded positively to using Quillbot to assist them in improving the quality of their writing. Furthermore, the use of Quillbot was found to have three benefits: enhancing students' positive attitudes toward writing, providing a variety of user-friendly writing features, and aiding students' language development. This study implies that AI-powered technology like Quillbot in writing, particularly in academic writing, has a significant role in creating high-quality writing for students.